Color-Color Diagrams in Near Infrared: (J-H)/(H-K). I. - Gyulbudaghian, A. L.; Baloian, N.; Sanchez, I. A.
In the paper are presented the color-color diagrams (J-H)/(H-K) for all stars with visible values B<11, for which in the known catalogs the values of J, H, K, and also spectral classes and luminosity classes of these stars are given. The diagrams are constructed for luminosity classes Ia, Ib, II, III, IV, V. The similarity of diagrams for classes Ia and Ib (super giants) and II (giants), is obvious from these diagrams. The diagrams obtained by us can be used for discovering of new young stars and also for determining of color excesses of investigating stars. Maximal amounts of stars are registered in the classes V and III. There is a tendency of increasing of J-H and H-K along the sequence of spectral classes O – M, which is correct for all luminosity classes.
Keywords: Stars